Językowe, muzyczne i psychologiczne oblicza kobiecości w Siostrze Angelice Giacomo Pucciniego (Conversatoria Linguistica, 2020)
The present paper discusses the linguistic, musical and psychological aspects of female characters in Giacomo Puccini’s Suor Angelica. The authors focus particularly on the central image of the opera, entitled Aunt Princess (La Zia Principessa). An interdisciplinary approach to the subject was possible thanks to the competences of authors on the field of literature, libretto and music as well as psychology and music theory.